Chiral Aminophosphines as Catalysts for Enantioselective Double-Michael Indoline Syntheses - Ohyun Kwon; San N. Khong (Molecules, 2012)
The bisphosphine-catalyzed double-Michael addition of dinucleophiles to electron-deficient acetylenes is an efficient process for the synthesis of many nitrogen-containing heterocycles. Because the resulting heterocycles contain at least one stereogenic center, this double-Michael reaction would be even more useful if an asymmetric variant of the reaction were to be developed. Aminophosphines can also facilitate the double-Michael reaction and chiral amines are more readily available in Nature and synthetically; therefore, in this study we prepared several new chiral aminophosphines. When employed in the asymmetric double-Michael reaction between ortho-tosylamidophenyl malonate and 3-butyn-2-one, the chiral aminophosphines produced indolines in excellent yields with moderate asymmetric induction.